Pengaruh Penerapan e-SPT PPN terhadap Kualitas Informasi (Survei Pada KPP Pratama Cimahi) - Khamid, Abdul (Jurnal Riset Akuntansi, 2015)
The purpose of this research was to determine how much influence the e-SPT PPN to the information quality. The method used in this research is descriptive method with using explanatory survey, verification with quantitative approach. With a population of 46 and sample of 32 respondent. The test statistic used is the calculation of validity and relibility testing using software SPSS 19.0 for windows. Results of testing the hypothesis in this study show that (1) the implementation of e-SPT PPN has an influence on the information quality. Keywords: e-SPT PPN, Information Quality